Direct immunofluorescence study in patients with lichen planus - Kanokvalai Kulthanan (2018)
Background: Direct immunofluorescence (DIF) studies in patients with lichen planus (LP) show the deposition of multiple immunoglobulins (Igs) at the cytoid bodies (CBs) and fibrin at the dermoepidermal junction (DEJ). The deposition of Ig at the DEJ, as in patients with lupus erythematosus (LE), is occasionally found. For cases with no specific clinical and histologic characteristics, or with ambiguous features, DIF studies may be helpful in disease differentiation. Methods: From 1996 to 2004, data from 72 patients with LP, diagnosed on the basis of clinical and histologic criteria at the Department of Dermatology, Siriraj Hospital, Bangkok, Thailand, were collected. The results of DIF studies were analyzed. Results: Deposits at the DEJ and CBs were detected in 53% and 60% of cases, respectively. A combination of DEJ (mostly fibrin) and CB (mostly IgM) deposits was found in 38% of cases. A combination of IgM and other immunoreactant deposits, including fibrin at the CBs, was found in 56% of cases. Conclusions: This study showed that the positive yield of DIF in LP was 75%. Shaggy fibrin deposition at the DEJ, which is the single best indicator in the diagnosis of LP, was found in 56% of cases. The presence of CBs only, which is a poorer indicator than the shaggy deposition of fibrin along the DEJ, was found in 22% of cases. There were no statistically significant differences in positive DIF yield between specimens derived from glabrous skin and oral lesions (P = 0.67). Forty-four per cent of cases had immunoreactants other than fibrin deposited along the DEJ, which resembled those of LE. © 2007 The International Society of Dermatology.